Does malnutrition influence outcome in children undergoing congenital heart surgery in a developing country? - Eva M. Marwali; Sekarpramita Darmaputri; Dadang H. Somasetia; Sudigdo Sastroasmoro; Nikolaus A. Haas; Michael A. Portman (Paediatrica Indonesiana, 2015)
Background Most children undergoing cardiac surgery forcongenital heart disease (CHD) in developing countries aremalnourished. Malnutrition is known as a co-morbidity factorthat might predict and influence outcomes after surgery.Objectives To evaluate the effect of malnutrition and otherassociated risk factors on post-operative outcomes in childrenwith CHDs underwent cardiac surgery.Methods We conducted a retrospective cohort study in a singlecenter tertiary pediatric cardiac intensive care unit (PCICU)in Indonesia. Our cohort included all children between 5 and36 months of age undergoing congenital heart surgery withcardiopulmonary bypass from November 2011 until February2014. Outcomes measured were the length of intubation and thelength of ICU stay. Variables for potential influence investigatedwere the nutritional status, age, gender, type of cardiac anomaly(acyanotic vs. cyanotic), Aristotle score, cardiopulmonary bypasstime, aortic cross-clamp time, and Pediatric Risk of Mortality(PRISM) III score.Results Out of 249 patients included, 147 (59%) showedmalnourishment on admission. Malnourished patients weresignificantly younger in age, presented with an acyanotic heartdefects, and had higher PRISM III score. Additionally, they alsohad a longer mechanical ventilation time and ICU stay thanthose with a normal nutritional status. After adjusting for variousvariables using a multiple logistic regression model it could bedemonstrated that a higher Z-score for weight to age was asignificant protective factor for the intubation time of more than29 hours with an odds ratio of 0.66 (95% CI 0.48 to 0.92, P =0.012). Non-malnourished patients had a 49% significantly higherchance for extubation with a hazard ratio of 1.49 (95% CI 1.12to 1.99, P= 0.007).Conclusion Malnourishment is clearly associated in a linearfashion with longer mechanical ventilation and ICU stay. As one ofsignificant and potentially treatable co-morbidity factors, preventionof malnourishment by early diagnosis and optimal timing for surgeryis important.